2016
DOI: 10.4172/2157-7412.1000285
|View full text |Cite
|
Sign up to set email alerts
|

Association of Superoxide Dismutase 2 Polymorphism Rs4880 and Open-Angle Glaucoma in a Greek Patients’ Cohort

Abstract: Purpose: Glaucoma is a multifactorial optic neuropathy and leading cause of visual impairment and blindness. Multigenic inheritance hypothesis is being investigated over the past decades and numerous mainly causative and synergic polymorphisms have been revealed. Aim of this study is to investigate whether superoxide dismutase 2 (SOD2) polymorphism rs4880 is associated with primary open angle glaucoma (POAG) in Greek population. Materials and method:This is a case control study of 106 POAG patients and 120 tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, it has been suggested that GSTM1-null genotype is an important genetic risk factor for gastric, lung and colorectal cancer development [31,32]. Another pathology that has been associated with GSTM1 polymorphisms is glaucoma, with increased incidence of primary open-angle glaucoma (POAG) in the null variant [33]. Similarly, the GSTM1-null genotype is linked to an elevated risk of POAG in smokers, according to a study by Stamenkovic et al, suggesting a possible gene-environment interaction [34] and a meta-analysis by Yu et al demonstrated that combinations of GST polymorphisms are linked to an increased risk of glaucoma [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that GSTM1-null genotype is an important genetic risk factor for gastric, lung and colorectal cancer development [31,32]. Another pathology that has been associated with GSTM1 polymorphisms is glaucoma, with increased incidence of primary open-angle glaucoma (POAG) in the null variant [33]. Similarly, the GSTM1-null genotype is linked to an elevated risk of POAG in smokers, according to a study by Stamenkovic et al, suggesting a possible gene-environment interaction [34] and a meta-analysis by Yu et al demonstrated that combinations of GST polymorphisms are linked to an increased risk of glaucoma [35].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 11 publications (14 case-control studies) involving 2,413 POAG patients and 1,904 controls focusing on rs166850 C/T and rs10451941T/C were included in this meta-analysis. [13][14][15][16][17][18][19][20][21][22][23] Eight of the studies were conducted on Caucasian descendants, three on Asian descendants and three on African descendants. For the control design, eight studies were conducted with population-based (PB) controls, four with hospital-based (HB) controls, and two with other individuals.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This result was not validated by the study conducted by Liu et al [139], which demonstrated no association between the OPA1 polymorphisms and a POAG phenotype that includes increased IOP in Caucasian, African American and Ghanaian populations. Several other studies also failed to demonstrate a correlation between OPA1 and NTG in Greek [140], Korean [141], African Caribbean [142], Chinese [143], Mexican [144], German [76], Singaporean and Indian patient populations [145].…”
Section: Opa1mentioning
confidence: 99%